Usulan Redesain Masjid At-Taqwa Desa Galeh Kecamatan Tangen Kabupaten Sragen Dengan Pendekatan Konsep Desain Neo Vernakular - riza susanti; Shifa Fauziyah; Ratih Widiastuti (Sekolah Vokasi Universitas Diponegoro, 2023)
A mosque or masjid is a place for muslims to pray. At-Taqwa mosque is the mosque of Galeh village and its existence is important for the villagers. However, due to many defects (damages) and limited capacity, the number of visitors is decreasing. A design recommendation was proposed by the study programme of Civil Infrastructure Engineering and Architectural Design, Department of Civil and Planning, Vocational School, Diponegoro University, through a community service programme. Using neo-vernacular concept design, five primary aspects were performed i.e. combining the concept of local roof and dome, applying symmetrical patterns for the façade, using roosters as wall opening in order to create geometrical patterns, adding the mosque’s tower, and terras that surrounding the mosque